1989
DOI: 10.1164/ajrccm/139.3.587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inhalable Particles on Respiratory Health of Children

Abstract: Results are presented from a second cross-sectional assessment of the association of air pollution with chronic respiratory health of children participating in the Six Cities Study of Air Pollution and Health. Air pollution measurements collected at quality-controlled monitoring stations included total suspended particulates (TSP), particulate matter less than 15 microns (PM15) and 2.5 microns (PM2.5) aerodynamic diameter, fine fraction aerosol sulfate (FSO4), SO2, O3, and No2. Reported rates of chronic cough,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
327
2
19

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 626 publications
(374 citation statements)
references
References 1 publication
26
327
2
19
Order By: Relevance
“…In each study, exposure -effects relationships can be derived for the pollution range encountered in the study and thus, a wide pollution range is favorable. The eight districts of this study exhibited a wide range for each concerned pollutant, as shown clearly in Figure 5 where the ranges from major previous US /Europe studies are also shown for comparison purposes (Ware et al, 1986;Dockery et al, 1989Dockery et al, , 1996Spengler et al, 1996;Braun -Fahrlander et al, 1997;Peters et al, 1999b;Pikhart et al, 2000 ). The comparison indicates that the data on pollution levels collected in this study substantially extended the upper end of the pollution ranges of major published studies.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In each study, exposure -effects relationships can be derived for the pollution range encountered in the study and thus, a wide pollution range is favorable. The eight districts of this study exhibited a wide range for each concerned pollutant, as shown clearly in Figure 5 where the ranges from major previous US /Europe studies are also shown for comparison purposes (Ware et al, 1986;Dockery et al, 1989Dockery et al, , 1996Spengler et al, 1996;Braun -Fahrlander et al, 1997;Peters et al, 1999b;Pikhart et al, 2000 ). The comparison indicates that the data on pollution levels collected in this study substantially extended the upper end of the pollution ranges of major published studies.…”
Section: Discussionsupporting
confidence: 69%
“…Annual means or multiyear means of air pollutants are often used in epidemiologic studies of long -term air pollution effects (Ware et al, 1986;Dockery et al, 1989;Peters et al, 1999a ). In each study, exposure -effects relationships can be derived for the pollution range encountered in the study and thus, a wide pollution range is favorable.…”
Section: Discussionmentioning
confidence: 99%
“…Because community air pollutants tend to be widely distributed, exposure subgroups within a region were difficult to distinguish. As a result, four studies distinguished exposure groups by areas with different measured pollutant levels (Ware et al, 1986;Dockery et al, 1989;Pope, 1991;Horstman et al, 1997 ). In four other studies, exposure groups were aggregated from populations of different areas with comparable pollutant levels (Schenker et al, 1983(Schenker et al, ,1986Dockery et al, 1996;Raizenne et al, 1996 ).…”
Section: Study Characterizationmentioning
confidence: 99%
“…The Two -Stage Method To avoid the problems in the non hierarchical method, we can aggregate individual health data to the same level as the pollution measures (Dockery et al, 1989 ). The first stage is therefore to calculate this aggregated measure.…”
Section: Three Approaches To Analysis In Hierarchical Studiesmentioning
confidence: 99%
“…Another method uses distance from a point source as the``dose'' (e.g., Bhopal et al, 1998;Dolk et al, 2000 ). A third uses the ambient air pollution within an area of residence as the estimate of exposure (e.g., Dockery et al, 1989;Zemp et al, 1999) . This third method requires a number of areas with differing levels of pollution, in order to have individuals at different exposures, and is increasingly used in the context of large collaborative projects.…”
Section: Introductionmentioning
confidence: 99%